THE EFFECT OF PROFITABILITY, LIQUIDITY, SOLVENCY, AND MARKET CAPITALIZATION ON THE COMPANY’S VALUE (A STUDY OF BASIC MATERIALS SECTOR STOCKS ISSI-INDEXED PERIOD 2019-2023) - Riza, Ira Febriliana Dewi; Slamet, Slamet; Suprayitno, Eko (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Using the ISSI-indexed stocks in the basic materials sector, this study seeks to ascertain how market capitalization, profitability, solvency, and liquidity affect company value as measured by PBV (price to book value) while making investment decisions. The performance of basic materials sector stocks showed an increase in 2020-2021, but a decline in performance in 2022-2023. This study employs a quantitative panel data regression technique with 245 data points from 49 businesses that fit the research sample requirements for the 2019–2023 timeframe . This study indicates that the variables ROA and Market Capitalization partially have a significant positive effect on firm value. Conversely, other variables do not significantly affect firm value. Simultaneously, the variables have a significant effect on the company. The adjusted R-squared value is 4.57%, indicating that the model cannot fully explain firm value. This study recommends additional analysis considering factors beyond the variables used to improve model accuracy.